A stochastic approach to the closure of accessible sets of control systems with application on homogeneous spaces - Ledesma, Diego S.; Silva, Fabiano B. da [UNESP] (Taylor & Francis Ltd, 2018)
Given a control system on a compact manifold M, we study conditions for the foliation defined by the accessible sets to be dense in M. For this, we relate the control system to a stochastic differential equation and, by the support theorem, we give a characterization of the density in terms of the infinitesimal generator of the diffusion and its invariant measures.
Keywords: Control systems; diffusion processes; stochastic calculus; Brownian motion